(3eONd JWHjbj(B-(3eJcGeds - (3Ydj adGM(B, (3GdRYHjs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ(B,s, 2015)
(3GdJhRjY hGdEeOGO,HjFI EOGQI GdJhRjY,ESJQGJjLjI EOGQI GdJhRjY,eGgjI bfhGJ GdJhRjY,GdhSWGA GdhXjajhf(B((3eDSSGJ GdSeGSQI hGdhcdGA(B)(3,GdhSWGA GdJLGQjhf(B((3eDSSGJ JLGQ GdJLRFI(B)(3,GdhSWGA GdJLGQjhf(B((3eDSSGJ JLGQI GdLedI,eGgjI fXGe GdJhRjY GdeGOj,bfhGJ JhRjY GdNOeGJ,bfhGJ GdJhRjY GdOhdjs
(3GdedGMb(B:(3U(B.355-388(3;HHdjhZQGajG(B:(3U(B.389-392s
Keywords: (3EOGQI GdCYeGds; (3GdJShjbs